Social Capital and Its Role in the Development of Tambi Coffee - Ratih Prananingrum (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
Agricultural development at various regional levels is largely determined by the active participation of all subjects of agricultural business actors both upstream and downstream. Main actors and business actors in agriculture play an important role in increasing products and productivity is also one of the indicators of the success rate of development in agriculture. The purpose of this study is to determine and interpret the forms of social capital that are owned by its use in the sustainability of the Tambi coffee business. The research methods used are in-depth interviews, observation, and documentation. The results of the study found that the social capital of Tambi coffee farmers was built with mutual trust in establishing good cooperative relationships, not only with fellow coffee farmers but also relationships with other parties. The sustainability of the coffee business is colored by norms found in daily life formed between coffee farmers, coffee entrepreneurs, and PT Geo Dipa Energi (Persero) Dieng Unit. They adhere to these norms together in their business activities to make a profit. There is a value of the spirit of learning and working hard which aims to increase productivity, the value of friendliness, cleanliness as a form of action to bind relationships with consumers and customers, and creativity as a value to overcome competition in business. The use of social capital also has an impact on the preservation of Tambi coffee, Wonosobo Regency.